2011
DOI: 10.1371/journal.pone.0020548
|View full text |Cite
|
Sign up to set email alerts
|

The Acceptability of Internet-Based Treatment and Characteristics of an Adult Sample with Obsessive Compulsive Disorder: An Internet Survey

Abstract: BackgroundObsessive-compulsive disorder (OCD) is a disabling anxiety disorder, but most individuals delay seeking treatment. Internet-based cognitive behavioural therapy (iCBT) is an innovative service delivery method that may help to improve access to care, but the acceptability to consumers of such programs has not yet been established.MethodologyPeople with symptoms of OCD were invited to complete an online survey enquiring about demographic characteristics, symptom severity, and acceptability of Internet-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
73
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 94 publications
(90 citation statements)
references
References 33 publications
12
73
1
1
Order By: Relevance
“…When it comes to patient attitudes data is not consistent and potentially there are differences between countries and settings, with some studies showing more positive attitudes Wootton et al, 2011] than others [Mohr et al, 2010]. A sixth important point is the role of healthcare regulation and reimbursement issues that are instrumental when implementing ICBT in clinical practice.…”
Section: Depressionmentioning
confidence: 99%
“…When it comes to patient attitudes data is not consistent and potentially there are differences between countries and settings, with some studies showing more positive attitudes Wootton et al, 2011] than others [Mohr et al, 2010]. A sixth important point is the role of healthcare regulation and reimbursement issues that are instrumental when implementing ICBT in clinical practice.…”
Section: Depressionmentioning
confidence: 99%
“…Also, a survey of primary health care patients showed that 92% were interested in face-to-face interventions, but only 48% in Internet treatment [6]. However, two surveys reported contrasting results [7,8]. For instance, Wootton et al [7] found that only 10% of individuals with high levels of obsessive-compulsive symptoms would prefer face-to-face treatment to online therapy.…”
Section: Tablementioning
confidence: 99%
“…However, two surveys reported contrasting results [7,8]. For instance, Wootton et al [7] found that only 10% of individuals with high levels of obsessive-compulsive symptoms would prefer face-to-face treatment to online therapy. These surveys involved self-selected samples in that they comprised individuals not necessarily seeking treatment who were accessing an online clinic website (www.virtualclinic.org.au).…”
Section: Tablementioning
confidence: 99%
“…However, almost half of the Internet sample indicated they had not received previous treatment for PTSD due to reasons such as lack of money, lack of response to previous treatment, and not perceiving their difficulties as severe enough for treatment. A similar study found that an Internet survey sample had comparable obsessivecompulsive disorder symptom severity to an outpatient clinic sample [35]. The Internet sample reported reduced time and costs, privacy and anonymity as the main advantages of accessing Internet treatments.…”
Section: Introductionmentioning
confidence: 74%